Tissue‐specific DNA levels and hyphal growth patterns of Hymenoscyphus fraxineus in stems of naturally infected Fraxinus excelsior saplings. Issue 3 (30th December 2015) - Matsiakh, I.; Solheim, H.; Nagy, N. E.; Hietala, A. M.; Kramarets, V.
Summary: Ten saplings of European ash ( Fraxinus excelsior L.) naturally infected by the invasive ash dieback pathogen Hymenoscyphus fraxineus were collected in Ukraine and Norway and examined for bark necrosis and extension of discoloration in sapwood and pith in a stem region. Tissue‐specific colonization profiles were determined by spatial analyses of symptomatic and visually healthy stem tissues using a H. fraxineus‐ specific qPCR assay and light microscopy. Our data suggest that hyphal growth in the starch‐rich perimedullary pith is of particular importance for both axial and radial spread of H. fraxineus, but that most of its biomass accumulates in sapwood parenchyma. The study confirms the results from earlier work and presents new information that refines the current stem invasion model.